Endometriosis and uterine malformations: infertility may increase severity of endometriosis. (11th November 2016) - Boujenah, Jeremy; Salakos, Eleonora; Pinto, Mélodie; Shore, Joanna; Sifer, Christophe; Poncelet, Christophe; Bricou, Alexandre
Abstract: Introduction: The aim of our study was to compare the stage and severity of endometriosis in fertile and infertile women with congenital uterine malformations. Material and methods: We performed an observational study from September 2007 to December 2015 in a tertiary care university hospital and assisted reproductive technology center. A total of 52 patients with surgically proven uterine malformations were included. We compared 41 infertile patients with uterine malformations with 11 fertile patients with uterine malformation. The main outcome was the stage, score and type of endometriosis in regard to infertility and class of uterine malformation. Results: The rate of endometriosis did not differ between the two groups (43.9 vs. 36.4%). The mean revised American Fertility Society score was higher in infertile patients with uterine malformations (19.02 vs. 6, p < 0.05). No significant difference was found in the rate of superficial peritoneal endometriosis (43.9 vs. 37.5%). Endometrioma and deep infiltrating endometriosis were associated with uterine malformations in infertile women, respectively 14.6 and 0%. No difference in the characteristics of endometriosis was found regarding the class of malformation. Conclusions: The association of uterine malformations and infertility may increase the severity of endometriosis and raise the issue of their diagnosis and management.